»Gemeinde« als Projektionsfläche für Hoffnung und Verlust: Kirchentheoretische Erkundungen zur Funktion von »Gemeinde« im Kirchenreformprozess der EmK - Bühler, Maximilian (Theologie für die Praxis, 2025)
This paper explores the multifaceted meanings of »congregation« within the reform process in the Southern Annual Conference of the United Methodist Church (Germany). It reconstructs how »congregation« functions as an empty signifier which became a projection surface for both hopes and losses, highlighting its theological and organizational meanings. Based on empirical analysis, the study reveals conflicting visions and the impact of shifting paradigms - from community to encounter, from congregation to a network of local churches.